Bicitaxismo: transporte alternativo como propuesta para su articulación al sistema de transporte público de bogotá (2018)
The bicitaxismo like nonmotorised alternative means of transport, operates in Bogota (Colombia) from the unmannerliness. Nevertheless, widely it has been guaranteed by the citizenship and every time one extends to residential zones of diverse sectors of the capital to respond to demands of transport not satised by other formalized ways of collective public transport.  In this sense, the present article sets out the results of an investigation of case advanced on the bicitaxismo in the locality of Kennedy, sector that concentrates the greater number of bike-taxis and operators in the city, with support of the Seed plot of Investigation VITRA of the University the Great Colombia. It is analyzed if in the zone of study in mention, safe conditions of operation to passengers, operators and other road actors of the bicitaxismo are offered. The affectations to the mobility and the conditions of road safety are identied, derivatives of the implementation of this service. Another type of analyzed affectations, corresponds to the infrastructure of secondary routes, cycle-routes and bike-tracks. Through study, one looks for to make possible discussion scenes, in which the idea is refuted that the bicitaxismo is a competition for other ways of transport. In this way, he hopes himself to make possible the formalization and inclusion in the integrated system of public transport of the city.